Endothelial cells derived from non-malignant tissues are of limited value as models for brain tumor vasculature - Lohr, Jennifer; Mock, Andreas; Beckhove, Philipp; Herold-Mende, Christel (Anticancer research, 2015)
Background: Human umbilical cord vein endothelial cells (HUVECs) are commonly chosen over freshly isolated endothelial cells from glioblastomas (GECs) due to accessibility and costs. Materials and Methods: To test their suitability for in vitro studies, we comprehensively compared the transcriptomes and responses to major angiogenic cytokines of HUVECs (n=2) and GECs (n=5). Purity of GEC cultures was confirmed by uptake of acetylated low-density protein and immunostaining. Results: Unsupervised analysis revealed a distinct grouping. We identified 854 differentially expressed genes. Pathway and gene ontology enrichment analyses pointed to clear differences in angiogenesis and leukocyte transmigration. Comparing the expression of cell adhesion molecules in five major angiogenic cytokines revealed that HUVECs in contrast to GECs did not exhibit a previously described down-regulation of cell adhesion molecules upon incubation with transforming growth factor betas, but rather with basic fibroblast growth factor. Conclusion: Given our findings, we strongly recommend the use of GECs as model cells for brain tumor endothelium for experiments investigating angiogenesis and immunobiology.